Neonatal vitamin D status and risk of multiple sclerosis: A population-based case-control study. (3rd January 2017) - Nielsen, Nete Munk; Munger, Kassandra L.; Koch-Henriksen, Nils; Hougaard, David M.; Magyari, Melinda; Jørgensen, Kristian T.; Lundqvist, Marika; Simonsen, Jacob; Jess, Tine; Cohen, Arieh; Stenager, Egon; Ascherio, Alberto
Abstract : Objective: As previous research has suggested that exposure to vitamin D insufficiency in utero may have relevance for the risk of multiple sclerosis (MS), we aimed to examine the direct association between level of neonatal vitamin D and risk of MS. Methods: We carried out a matched case-control study. Dried blood spots samples (DBSS) belonging to 521 patients with MS were identified in the Danish Newborn Screening Biobank. For every patient with MS, 1–2 controls with the same sex and birth date were retrieved from the Biobank (n = 972). Level of 25-hydroxyvitamin D (25[OH]D) in the DBSS was measured using liquid chromatography tandem mass spectroscopy. The association between different levels of 25(OH)D and risk of MS was evaluated by odds ratios (OR) calculated in conditional logistic regression models. Results: We observed that lower levels of 25(OH)D in neonates were associated with an increased risk of MS. In the analysis by quintiles, MS risk was highest among individuals in the bottom quintile (<20.7 nmol/L) and lowest among those in the top quintile of 25(OH)D (≥48.9 nmol/L), with an OR for top vs bottom of 0.53 (95% confidence interval [CI] 0.36–0.78). In the analysis treating 25(OH)D as a continuous variable, a 25 nmol/L increase in neonatal 25(OH)D resulted in a 30% reduced risk of MS (OR 0.70, 95% CI 0.57–0.84). Conclusion: Low concentrations of neonatal vitamin D are associated with an increased risk of MS. In light of the high prevalence of vitamin D insufficiency among pregnant women, our observation may have importance for public health.